Does monetary policy affect real output in a supply-constrained economy: case of Malawi - Chingoli, Chionetsero Bartwell (School of Economics, 2018)
In a low income economy with a relatively undeveloped financial sector, the normal monetary policy instruments may not have the anticipated desired impact. In particular, economies that may be relatively supply constrained may not respond to money policies as anticipated, owing to a lack of flexibility in the system from economic and institutional constraints. In this case, monetary policies that might otherwise affect the creation of capital for investment and a robust environment for businesses to thrive may not occur. We consider the case of Malawi, which is acknowledged to have a number of supply-side constraints including those related to electricity production and water for agricultural production. We begin with a Cobb-Douglas type production function for the country, which includes droughts, owing to its effect on both electricity production and agriculture. This underlying production function provides an estimate of the long-run supply capacity based on capital, labour and water constraints. In a second stage of the model, we use the Engle-Granger approach to estimate a modified Error Correction Model (ECM) for a short-run growth equation, where we include the movements in monetary variables to test the impact of monetary policy on growth. We estimate our models in EViews for the period 1980 to 2014. Our estimated long-run production function shows that drought depresses real output, and capital and labour have roughly equal importance as factors of production. We then estimate a short-run growth equation using the ECM methodology and find that real exchange rate and real interest rate do not have a significant impact on growth although they have the anticipated sign. We also find that net credit to government and net credit to private sector negatively affect the growth in real output. Although the econometric results are not strong, we note that Malawi has had a history of volatile inflation, which appears to have negative impacts on real output. We believe that our results highlight the importance of more stable management of the money supply, as the monetarism school of thought would propose. We also note that government has been responsible for prolonged fiscal deficits and high borrowing, which may be a cause of the volatile monetary growth. Thus greater coordination of fiscal and monetary policies are needed to create smoother growth and inflation paths.